Rafting Expedition at Pahang River A Pictorial Journey - Said, Ismail (Faculty Built Environment, UTM, 2012)
Prefabricated timber raft is water-based recreational vehicle for drifting on rivers without rapids. It is a floating deck measuring 4.5m (length) X 3.2m (width) with a carrying capacity of 800 to 900 kg; appropriate for eight adults. It is made up of three major components: (1) float made from eight polyethylene drums, (2) frame made from timber boards (50X50mm), and (3) deck made from three pieces of 4mm thick waterproof plywoods. The drums and timber boards can be made from used materials whereas new plywoods are required for safety and durability. Minor components such as oars, masts, canvas and a stowage compartment are installed to facilitate the rafting crew in their expedition. The fundamental scheme of this raft is that it can be assembled or dismantled by eight adults within 25 minutes, costing RM650-800 and can be utilized for more than five times. It is a cheap recreational and eco-friendly mode to spend leisure activities without causing pollution to the river. The minimum drift duration is four days with average drifting speed of 4.2km/h covering a distance of 30 to 35 km per day.